Comparison of field measurement methods of nitrous oxide soil emissions: from the chamber to the vial - Cosentino, Vanina Rosa Noemi; Romaniuk, Romina Ingrid; Lupi, Ana Maria; Gomez, Federico M.; Rimski-Korsakov, Helena; Alvarez, Carina R.; Ciarlo, Esteban Ariel (Sociedade Brasileira de Ciencia do Solo, 2020)
Nitrous oxide (N2O) is a greenhouse gas that contributes substantially to global climate change. The N2O soil emissions have a large uncertainty because of its low atmospheric concentration levels and enormous spatial and temporal variability, which hinders its correct field measurement. For this reason, there are many papers focused on improving the N2O measurements in the field, which focus on different parts of the measurement process. However, no studies have focused on determining the appropriate method, in terms of simplicity and precision, for the sample extraction from inside of the chambers and its transfer to the storage vials, although this step is key in the sampling process. This study aimed to assess and compare the accuracies of three simple and economical methods in transfer soil emitted N2O from inside of the chambers to the vials. For this, a highly accepted method (vacuum by manual pump) and two simpler alternative methods (gas exchange by displacement and vacuum by syringe) were compared. Thirty static chambers were assessed with the quantified N2O emission values varied from 0 to 450 µg m-2 h-1 of N-N2O. Out of the three assessed methods, the vacuum method through the use of a manual vacuum pump was the best to quantifying N2O soil emissions (capturing 57 % of the highest emission values), followed by the gas exchange method by displacement (30 %), and finally by the vacuum method by syringe extraction (13%).